Comparison of nanocrystalline cellulose dispersion versus surface nucleation in poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) crystallization. (11th September 2020) - Haham, Hai; Shen, Mo‐Yuan; Billington, Sarah L.; Frank, Curtis W.
Abstract: Nanocrystalline cellulose (NCC), which is a known crystal nucleating agent, is utilized to improve poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) (PHBV) thermal properties. Since NCC aggregation in PHBV negatively affects composite properties and processability, NCC crystal nucleation effectiveness was examined at low concentrations (<1%) under isothermal and nonisothermal conditions. NCC was dispersed in PHBV solutions using a solvent exchange method and then cast into films. We found that NCC was an effective nucleating agent in amounts as low as 0.25%, resulting in an increase in PHBV crystallization rate by more than 50%. However, increasing to 1% NCC resulted in aggregation in PHBV, with the NCC becoming less effective compared to lower NCC concentrations. In an attempt to improve NCC dispersion, we added cellulose acetate (CA) or stearic acid (SA) to the casting solution, anticipating that CA or SA would preferentially adsorb on the NCC. With such pretreatment, dispersion was indeed improved but NCC became less effective as a PHBV nucleating agent. This work shows the advantage of using low NCC concentrations (<0.5%) for promoting PHBV crystallization, but the lack of improved nucleation upon addition of CA and SA supports the importance of NCC surface accessibility. Abstract : NCC as nucleating agents for PHBV: surface modified versus unmodified